Picturing heaven in early China - Tseng, Lillian Lan-ying (Harvard East Asian monographs ;, 2011)
Tian, or Heaven, had multiple meanings in early China. It had been used since the Western Zhou to indicate both the sky and the highest god, and later came to be regarded as a force driving the movement of the cosmos and as a home to deities and imaginary animals. By the Han dynasty, which saw an outpouring of visual materials depicting Heaven, the concept of Heaven encompassed an immortal realm to which humans could ascend after death. Using excavated materia.